Chk1 suppression leads to a reduction in the enhanced radiation-induced invasive capability on breast cancer cells. (14th June 2021) - Adachi, Takanori; Zhao, Wantong; Minami, Kazumasa; Yokoyama, Yuhki; Okuzaki, Daisuke; Kondo, Rika; Takahashi, Yutaka; Tamari, Keisuke; Seo, Yuji; Isohashi, Fumiaki; Yamamoto, Hirofumi; Koizumi, Masahiko; et al.
Abstract: Radiation therapy is generally effective for treating breast cancers. However, approximately 30% of patients with breast cancer experience occasional post-treatment local and distant metastasis. Low-dose (0.5 Gy) irradiation is a risk factor that promotes the invasiveness of breast cancers. Although an inhibitor of checkpoint kinase 1 (Chk1) suppresses the growth and motility of breast cancer cell lines, no study has investigated the effects of the combined use of a Chk1 inhibitor and radiation on cancer metastasis. Here, we addressed this question by treating the human breast cancer cell line MDA-MB-231 ( in vitro ) and mouse mammary tumor cell line 4 T1 ( in vitro and in vivo ) with γ-irradiation and the Chk1 inhibitor PD407824. Low-dose γ-irradiation promoted invasiveness, which was suppressed by PD407824. Comprehensive gene expression analysis revealed that low-dose γ-irradiation upregulated the mRNA and protein levels of S100A4, the both of which were downregulated by PD407824. We conclude that PD407824 suppresses the expression of S100A4. As the result, γ-irradiation-induced cell invasiveness were inhibited.